Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1124/dmd.114.062596
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling for Sequential Metabolism: Effect of CYP2C19 Genetic Polymorphism on Clopidogrel and Clopidogrel Active Metabolite Pharmacokinetics

Abstract: Clopidogrel is a prodrug that needs to be converted to its active metabolite (clopi-H4) in two sequential cytochrome P450 (P450)-dependent steps. In the present study, a dynamic physiologically based pharmacokinetic (PBPK) model was developed in Simcyp for clopidogrel and clopi-H4 using a specific sequential metabolite module in four populations with phenotypically different CYP2C19 activity (poor, intermediate, extensive, and ultrarapid metabolizers) receiving a loading dose of 300 mg followed by a maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…For example, the work published by Lee et al (2012) as well as Yousef et al (2013) primarily focused on the characterization of inactive metabolite kinetics, which is unlikely to be reflective of clopidogrel’s therapeutic effect. There are also studies (Djebli et al, 2015; Yun et al, 2014) that focus on an isolated PK or PD question or use parameterizations (e.g. nonlinear absorption processes to characterize saturable bioactivation) that are not physiologically relevant (Ernest et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the work published by Lee et al (2012) as well as Yousef et al (2013) primarily focused on the characterization of inactive metabolite kinetics, which is unlikely to be reflective of clopidogrel’s therapeutic effect. There are also studies (Djebli et al, 2015; Yun et al, 2014) that focus on an isolated PK or PD question or use parameterizations (e.g. nonlinear absorption processes to characterize saturable bioactivation) that are not physiologically relevant (Ernest et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using another method proposed by Turner et al (2006), the predicted unbound fraction of clopidogrel and 2-oxo-clopidogrel in the microsomal system was 0.74 (0.83–1.54 μM) and 0.97 (1.57–27.0 μM), respectively. However, a recent published clopidogrel PBPK model developed with Simcyp (Djebli et al, 2015) reported that the estimated unbound fraction values 0.015 and 0.18, which turned out to best characterize unbound fraction of clopidogrel and 2-oxo-clopidogrel in the microsomal system, respectively, were significantly lower than the unbound fraction values obtained from prediction methods derived from historical data (Hallifax and Houston, 2006; Turner et al, 2006); and the resultant unbound K m values were 0.017–0.039 μM and 0.29–5.00 μM for step 1 and step 2 of the 2-step clopidogrel bioactivation process, respectively. Interestingly, this set of unbound K m values (0.017–5.00 μM) was within the same range of our model estimated free in vivo K m value (0.154 μM), which is a lumped value that characterizes the overall 2-step bioactivation process, indicating that our model may provide a reasonable characterization of free in vivo K m value.…”
Section: Discussionmentioning
confidence: 99%
“…A well‐stirred model accounting for nonspecific in vitro binding ( fu inc ), blood to plasma ratio (B/P), and the fraction unbound in plasma ( fu p ) best described CLOP's hepatic biotransformation to CLOP‐AM (A 5 ) via the formation of CLOP intermediate metabolite, 2‐oxo‐clopidogrel (2‐OC) (A 4 ) in the liver. The model also accounted for the mechanism of hydrolytic inactivation of CLOP and its metabolites by CES1 ( Figure ) ( Supplementary Table S1 ) . Governed by the law of mass balance, our model described the change over time in amount of CLOP (A 3 ) and CLOP‐AM (A 6 ) in the systemic circulation and the corresponding change in MPA, normalized to MPA 0 (A 7 ) due to irreversible binding of CLOP‐AM to the circulating platelets.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard a useful mechanistic modeling tool that can be applied to accomplish this objective involves physiologically based pharmacokinetic (PBPK) modeling and simulation, which provides a quantitative framework to assess potential DDI . In addition, recent advances in PBPK modeling and simulation have enabled this approach to be used as a mechanistic modeling tool for the evaluation of the possible impact of various intrinsic and extrinsic factors affecting the pharmacokinetics of drugs such as drug‐disease interactions in organ impairment patients, pharmacogenetics, drug formulation, and pediatrics …”
mentioning
confidence: 99%